Decrease in the number and apoptosis of alveolar bone osteoclasts in estrogen-treated rats - Faloni, A. P. S.; Sasso-Cerri, E.; Katchburian, E.; Cerri, Paulo Sérgio [UNESP] (Blackwell Publishing, 2007)
Bone is a mineralized tissue that is under the influence of several systemic, local and environmental factors. Among systemic factors, estrogen is a hormone well known for its inhibitory function on bone resorption. As alveolar bone of young rats undergoes continuous and intense remodeling to accommodate the growing and erupting tooth, it is a suitable in vivo model for using to study the possible action of estrogen on bone. Thus, in an attempt to investigate the possibility that estrogen may induce the death of osteoclasts, we examined the alveolar bone of estrogen-treated rats.Fifteen, 22-d-old female rats were divided into estrogen, sham and control groups. The estrogen group received estrogen and the sham group received corn oil used as the dilution vehicle. After 8 d, fragments containing alveolar bone were removed and processed for light microscopy and transmission electron microscopy. Sections were stained with hematoxylin and eosin and tartrate-resistant acid phosphatase (TRAP)-an osteoclast marker. Quantitative analysis of the number of TRAP-positive osteoclasts per mm of bone surface was carried out. For detecting apoptosis, sections were analyzed by the Terminal deoxynucleotidyl transferase-mediated dUTP Nick-End Labeling (TUNEL) method; TUNEL/TRAP combined methods were also used.The number of TRAP-positive osteoclasts per mm of bone surface was significantly reduced in the estrogen group compared with the sham and control groups. TRAP-positive osteoclasts exhibiting TUNEL-positive nuclei were observed only in the estrogen group. In addition, in the estrogen group the ultrastructural images revealed shrunken osteoclasts exhibiting nuclei with conspicuous and tortuous masses of condensed chromatin, typical of apoptosis.Our results reinforce the idea that estrogen inhibits bone resorption by promoting a reduction in the number of osteoclasts, thus indicating that this reduction may be, at least in part, a consequence of osteoclast apoptosis.
Keywords: alveolar bone; estradiol; osteoclast; programmed cell death